THE IMPORTANCE OF ESP MATERIAL DEVELOPMENT FOR POLYTECHNIC STUDENTS - Sri Endah Kusmartini; Risnawati Risnawati; Risa Risa; Darmaliana Darmaliana (HOLISTICS, 2019)
Abstract: The availability of instructional material is very important to support teaching and learning process as well as to improve academic achievement of the students. The objectives of this research were to find out the importance of ESP material development especially speaking materials for the students of English Department State Polytechnic of Sriwijaya based on the viewpoints of the students and the viewpoints of the teachers; what should be considered in developing ESP materials especially speaking materials for the students of English Department State Polytechnic of Sriwijaya; and how to develop ESP materials especially speaking materials for the students of English Department State Polytechnic of Sriwijaya. The respondents of this research were 12 student respondents, 3 teacher respondents, the management of the institution, and 2 experts in education and educational technology. The data were collected by using in depth-interview and analyzed by using descriptive analyses. The results revealed that ESP materials especially speaking materials for the students of English Department State Polytechnic of Sriwijaya were important to be developed to fulfill the needs of specific purposes; the factors that should be considered in developing ESP materials especially speaking materials for the students of State Polytechnic of Sriwijaya were students’ needs, the institution needs, and the users’ needs, authenticity of the text and the task, and personal touch; ESP material developer especially speaking material developer can use many kinds of R & D models like the small scale project of R & D proposed by Gall, Borg, and Gall (2003).